Biological kinetics evaluation of anaerobic stabilization pond treatment of palm oil mill effluent - Wong, Yee Shian; Mohd Omar, A.B. Kadir; Tjoon, Tow Teng (Elsevier Ltd., 2009)
Link to publisher's homepage at http://www.elsevier.com